Effects of college students’ mindfulness on depression symptoms during the epidemic prevention and control period: The mediating effect of psychological resilience - Jiang, Yanfei; Yi, Zhiyu; Yao, Youjuan; Hu, Yanbing; Li, Feilin; Ma, Huizhen (Frontiers in Psychiatry, 2023)
Depression symptoms significantly impact college students’ mental health, particularly during the “closed management” period during the spread of COVID-19. Exploring the mechanism that affects college students’ depression symptoms can help alleviate the impact of Closed management policies on individual mental health and improve their mental health level. The onset of the COVID-19 pandemic resulted in the normalization of epidemic prevention and control in China and the implementation of the dynamic zero-COVID policy. This study used the Five-Factor Mindfulness Questionnaire - Short Form, Psychological Resilience Scale, and Beck Depression Scale to investigate the mindfulness, psychological resilience, and depression symptoms of 1,062 students under closed management conditions at Northwest Normal University. The mindfulness, psychological resilience, and depression status of students in closed management were investigated using an online questionnaire survey. Eight hundred and ten college students (Mage = 20.43, SD = 1.67, Range = 17−30) were selected to test the model using the structural equation model and bootstrap method. The results showed that the gender differences in mindfulness and psychological resilience were not significant. Gender differences in depression symptoms were significant, and depression symptoms in men were significantly higher than in women. Grade differences in resilience, mindfulness, and depression levels were not significant. Thus, psychological resilience is negatively associated with depressive symptoms. Psychological resilience plays a mediating role between mindfulness and depressive symptoms. This study provides reference and inspiration for improving college students’ mental health under epidemic prevention and control circumstances.